(untitled) (Филолошки студии, 2019)
This paper deals with a very important period in the history of Macedonian schools in 19th century. Education of women in 19th century is to a degree lower than that of men. This was so because there were not enough teachers that could lead to education. By the mid-19th century, there was not a greater interest in the education of female children in Macedonia. This situation was characteristic for the entire Macedonia. In mid-19th century, there were female secular schools in cities economically rich as were: Veles, Bitola, Salonica, Prilep, Stip and others. Female education began to make progress. Many have understood that the educated women are more useful in raising future generations.